Risk assessment of heavy metals in soils contaminated by smelting waste for the perspective of chemical fraction and spatial distribution - Zeng, Xiaoxi; Chen, Qiming; Tan, Qin; Xu, Hong; Li, Wen; Yang, Sheng; Wang, Jianhui; Ren, Jiali; Luo, Feijun; Tang, Jianxing; Wu, Ling; Zhang, Yuanke; et al. (Journal of Environmental Engineering and Landscape Management, 2021)
The heavy metals contamination in soil has attracted increasing attention. In this study, the main objective was to determine three heavy metals (Cd, Pb, and Cr) of soils contaminated by smelting waste, and to evaluate pollution risk. The Pb (15.48 mg/kg) and Cd (311.39 mg/kg) mean concentrations exceeded the national standard, while Cr (48.60 mg/kg) concentration did not exceed. The Heavy metal fractions analysis showed that three heavy metals were dominated by FeMn oxides fraction (Fe-Mn). The correlation and cluster analysis indicated that there was significant correlation between Cd and Pb (0.55< r < 0.96), while Cr was not correlation to Cd and Pb. The environmental pollution of heavy metals was assessed by the ratio of secondary phase and primary phase (RSP). The result showed that RSP values of Cd, Pb, and Cr range from 13.05–54.28, 16.11–4.97 and 1.61–52.33, which indicated soil was serious contaminated by them. These results showed that smelting waste discharge led to this smelter soil being seriously contaminated by multiple heavy metals which have a tendency to transport and accumulate into deep soil due to their high fractional transformation.